The THE ORGANIZATIONAL OF CULTURE AND INTEGRITY THAT IMPACT TO THE WORK EFFECTIVENESS OF STATE CIVIL EMPLOYEES (ASN) OFFICE OF FOOD SECURITY AND AGRICULTURE (DISKANTAN) KUNINGAN DISTRICT - Renaldi Mahmud, Renaldi Mahmud; Erna Rusmiwati Sukandar; Ridwan Hakiki (Nusantara Journal Of Management Business (NUMABI), 2025)
The problem in this study is related to the Work Effectiveness of ASN Employees in the Office of Food Security and Agriculture which is influenced by Organizational Culture and Integrity. This study aims to determine the influence of Organizational Culture and Integrity on the Work Effectiveness of ASN Office Employees in 2023. The method used in this study is quantitative descriptive. This study used primary data by distributing questionnaires measured by Likert scale research instruments. The samples in this study amounted to 60 samples, namely all ASN employees of the Office of Food Security and Agriculture of Kuningan Regency. The analysis tool used is multiple linear regression analysis. The results of this study showed that the influence of Organizational Culture and Integrity on employee performance was 43.1% while the remaining 56.9% was influenced by other factors that were not examined in this study.